THE CONCEPT OF THE FRITIOF (FTF) MODEL - Dustmurodov, E.E; Dustmurodova , X.E (Innovative Development in Educational Activities, 2023)
The FRITIOF model, or FTF for short, is used in Geant4 to model hadron-nuclear interactions with Plab > 3-4 GeV/s, core-nuclear interactions with Plab > 3-4 ГэВ/с/nucleon and anti-baryon-nuclear interactions, as well as anti-nuclear interactions without a low energy threshold. Since the model does not include multi-jet production in hadron-nucleon interactions, the upper limit of its reliability is about 1000 GeV/s. The main components of the model and its results are briefly described.